Pengaruh Hubungan Orangtua dan Anak dalam Pembentukan Karakter Anak - Gusti Asiyani; Siti Nor Asiah; Okta Sulistiyo Rina Hatuwe (Az-Zahra: Journal of Gender and Family Studies, 2023)
Children's golden age is a fundamental stage of personal development. At this stage, there are great opportunities for formation and growth of personality. When parents' role in shaping children's character and development becomes so great, it is not surprising that parents provide balanced (authoritative) parenting for their children, not authoritarian or tolerant parenting. This research aims to help parents understand their children's character to become disciplined and independent. This article uses the type of library research or library research, which is conducted to analyze data sourced from articles, books, magazines, newspapers, and other scientific works. This library research uses a qualitative approach. Based on the results of various studies, it is presented that the family is the first and foremost environment known by children, so it is in the family environment that the child's character and personality will be formed, which will also affect its development in the future, so by playing the proper role in educating and caring for children, children will grow and develop optimally. The most important thing is that children will grow up to be children with good character and personality.